Measuring the Concept of Restoration in Criminal Justice System - Asmadi Syam (Badan Strategi Kebijakan Hukum, 2022)
Regarding the restoration concept such as restorative justice, alternative dispute resolution, circle sentencing, and ishlah, Indonesia's Criminal Justice System is not yet familiar with this concept. Generally, the concept of restoration is not known in Criminal Procedure Law (KUHAP) which adheres to the principle of legality. Based on this situation, it is interesting to study the concept of restoration, especially the functionalization of restoration concepts and the readiness of the Indonesian Criminal Justice System to implement the restoration concept. This research used a qualitative research method that discusses the concept and implications of restoration associated with the applicable rules or principles. The results show that the restoration concept, such as alternative dispute resolution, circle sentencing, and ishlah, is a concept that prioritizes the interests of the parties involved, namely the principle of win-win solution and recovery. This concept has long been practiced by the community, especially indigenous peoples and in the Criminal Justice System. It has been functionalized to resolve criminal cases that meet the requirements of both the level of investigation and prosecution as a way of resolving criminal cases. The implications of these concepts on the Indonesian Criminal Justice System are deviations from the principle of legality in the KUHAP. However, these implications are logically acceptable to the community in the framework of equitable and definite legal manifestations. It is recommended that the mechanism for implementing the restoration concept, such as alternative dispute resolution, circle sentencing, ishlah, can be included in the Draft Criminal Procedure Code (RKUHAP). Thus, in the implementation, the restoration concept can be juridically and formally accepted as a principle of the Indonesian Criminal Justice System.